Preliminary contractual framework for BIM-enabled projects - Chong, Heap Yih; Fan, S.; Sutrisna, M.; Hsieh, S.; Tsai, C. (American Society of Civil Engineers, 2017)
Building information modeling (BIM) has entered into another phase of maturity, especially in countries that have been actively adopting and using BIM including in Taiwan, Republic of China. An effective management in BIM has increasingly become one of the demanding features in Taiwanese architecture, engineering, construction, and operation industries, particularly in dealing with the legal issues associated with BIM implementation. Therefore, the research aims to develop a preliminary contractual framework for BIM-based contract administration. Two objectives underpin the research, namely, (1) to identify the potential legal aspects that need to be considered in BIM-enabled projects, and (2) to determine the related contract provisions required in BIM contracts. The questionnaire survey method was adopted through a selective sampling approach in Taiwan. Thirty-six valid and completed questionnaires were analyzed. The results identify 21 related contract provisions that could potentially be used in BIM contracts. Following a thorough analytical discussion, these contract provisions were then incorporated into the developed contractual framework. While paving the way for a robust contractual mechanism for BIM-enabled projects in the future, the research contributes to the body of knowledge for BIM-based contract administration.